Depressive disorders and their correction in complex treatment of metabolic syndrome patients - Yu. P. Uspensky; E. V. Balukova (Кардиоваскулярная терапия и профилактика)
Aim. To study clinical and metabolic effects of selective serotonin re‑uptake inhibitor (SSTI) sertraline in complex treatment of metabolic syndrome (MS) patients. Material and methods. Thirty‑six MS patients were divided into two groups, according to treatment program and psychological symptoms. Intervention group received basic therapy and, in case of depressive disorders (DD) diagnosed, sertraline (50 mg/d), once per day in the morning, for 8 weeks. Control group received basic therapy only. In all participants, clinical, biochemical, and psycho‑physiological parameters were assessed. Results. DD of varying severity were diagnosed in 77,8% of MS patients. Clinical and metabolic MS symptoms correlated with depression severity. Adding sertraline to complex treatment was associated with hemodynamics stabilization, clinical and psychopathological symptom regression, glucose and serum lipoprotein level normalization. Conclusion. Adding sertraline to complex treatment of MS associated with DD improved therapy effectiveness and demonstrated beneficial clinical and metabolic effects.